Patient Role Clarity and Perceived Healthcare Quality Value: The Mediating effect of Patient Participation Behaviors - Siddig Balal Ibrahim; Tayseer Fadul Sidahmed; Tamer M. Alkadash; Ali Ateeq (RA JOURNAL OF APPLIED RESEARCH, 2026)
Purpose – Patient perceived quality value has become a critical concern. The purpose of this study is to develop and test an integrative model that examines the direct and indirect effects of patient role clarity on perceived healthcare quality value, mediated by the four dimensions of patient participation behaviors. Design/methodology /approach – A conceptual model, based on the role theory and service-dominant (S-D) logic, is proposed. The customer role clarity, perceived quality value and patient participation behaviors, including information seeking, information sharing, responsible behaviors, and personal interaction. All variables are measured from the patient’s perspective. A structural equation model is developed and tested on a purposive sample of 500 patients who had used the healthcare services in private hospitals in Khartoum state. Findings – The results reveal that patient role clarity positively influences both perceived quality value and all four dimensions of participation behavior. Among these behaviors, information seeking, responsible behavior, and personal interaction enhance perceived quality value, while information sharing shows no significant effect. Moreover, responsible behavior and personal interaction emerge as significant mediators between role clarity and perceived quality value, whereas information-related behaviors do not. Research limitations–This study is limited to private hospitals in Khartoum, Sudan, with data collected through convenience sampling, which restricts generalizability. Future research should explore other regions, service sectors, and customer role constructs, employ probability sampling, and examine broader dimensions of participation and value perceptions. Practical implications –This study offers practical value by showing that hospitals can enhance patients’ perceptions of healthcare quality by clarifying patient roles and actively fostering responsible behaviors and personal interactions, thereby improving both treatment outcomes and service experiences. Originality/value –This study uniquely integrates patient role clarity, participation behaviors, and perceived healthcare quality value, highlighting responsible behavior and personal interaction as key mediators and extending role theory and service-dominant logic to a developing-country healthcare context.